Neuroprotective effect of 7-geranyloxycinnamic acid isolated from Melicope lunu-ankenda (Gaertn.) T.G. hartley leaves in vitro - Mohamed, Mohamed, Zeinab Abdulwanis Masaoud (2020)
Neurodegenerative diseases (NDDs) are chronic and incurable conditions and have drawn robust attention of researchers due to their social and economic burdens. Lately, approximately 55 million people in the world were reported to suffer from one or more NDDs, notably a larger percentage suffers from AD because their longevity have increased. In Malaysia, the number of people with NDDs is projected to increase from 123,000 people in 2015 to be 261,000 by 2030 and will continue to increase to 590,000 people in 2050. Therefore, the strategies of using phytotherapeutic agents as alternative sources for NDDs therapy has become necessary. Several secondary metabolites have been isolated from Melicope lunu-ankenda (Gaertn.) T.G. Hartley plant (known in Malaysia as “tenggek burung”) leaves such as phenolic acid derivatives including 7-geranyloxycinnamic acid. However, the neuroprotective activity of 7-geranyloxycinnamic acid not studied till date. Thus, the aim of present study was to elucidate the in vitro neuroprotective activity of 7-geranyloxycinnamic acid isolated from M. lunu-ankenda leaves. In this regard, 7-geranyloxycinnamic acid was tested for neuroprotection on retinoic acid (RA)-induced differentiation of human neuroblastoma (SH-SY5Y) cell lines, and compared with curcumin, which was used as positive control in this study. SH-SY5Y cells were treated with 10 µM RA for 7-days, and then observed under a fluorescence microscope (phase contrast) to monitor differentiation and measure neurite length of undifferentiated and differentiated SH-SY5Y cell line. The differentiation of SH-SY5Y cell line was further ascertained by immunocytochemistry assay, whereby III β-tubulin (tuj-1) expression was detected by an Alexa fluorophore- 488 secondary antibody conjugate. Cell viability and neuroprotection were first assayed using 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide (MTT) reagent to determine the highest cell viability concentration of 7-geranyloxycinnamic acid, whereby the differentiated cells were pre-treated with serially diluted concentrations of 7-geranyloxycinnamic acid for ii 24, 48 and 72 hours before being exposed for 4 hours to H2O2 (300 μM). Annexin V-FITC assay by using flow cytometry and fluorescence microscopy by means of acridine orange and propidium iodide (AO/PI) double staining were employed to analyze the apoptotic inhibition ability of the compound on the differentiated cells. Surface morphological assessment and ultrastructural analysis were then conducted using scanning and transmission electron microscopy to evaluate the effect of the compound on surface morphology and internal features of the cells. The results showed that treatment of SH-SY5Y cells with RA for 7-days differentiated the cells into neurons and showed extended neurites, which was confirmed by the expression of class III β-tubulin (tuj-1) neuronal marker. Pre-treatment of neuronal cells with 7-geranyloxycinnamic acid (2.08 μM), particularly after 72 hours of treatment, significantly protected the differentiated SH-SY5Y cells against H2O2-induced apoptotic cell death, which was similar to the treatment of cells with 5.97 μM Curcumin plus 4 h exposure to H2O2 (300 µM). fluorescence microscopy after AO/PI staining showed neuroprotective activity of 2.08 μM 7-geranyloxycinnamic acid against nuclei damages due to H2O2 exposure that perhaps leads to cellular death via apoptosis, this figure is similar to what was observed when the cells were treated with curcumin prior to H2O2. The neuroprotective activity of 2.08 μM 7- geranyloxycinnamic acid against H2O2-induced apoptosis was ascertained by annexin V-FITC, whereby the cells pre-treated with either 7-geranyloxycinnamic acid or curcumin showed a low level of apoptosis and high cell viability. Surface morphology and internal features of the cells were appeared protected by 7- geranyloxycinnamic acid treatment, which were similar to those pre-treated with curcumin before H2O2 insult. The present finding suggested the neuroprotective potential of 7-geranyloxycinnamic acid on neuronal cells against H2O2-induced neurotoxicity, which was the first study discovered neuroprotective effect of 7- geranyloxycinnamic acid via mitochondrial pathway. Further analysis is recommended to assess the modulatory effect of 7-geranyloxycinnamic acid on gene and protein expression for genes and markers involved in Nrf2/ARE, IkB-α/NF-kB, MAPK and mitochondrial signaling pathways. Also, In vivo study in rats is recommended to further explain the neuroprotective effect of the compound.